UI/UX Design and Evaluation of Shrouded Buana Game Using Design Thinking and Cognitive Walkthrough - Sudaryanto, Aris; Ivaldy, Amsyar Raftan Oskash; Safrodin, Mohamad; Wijaya, Adi (Universitas Nahdlatul Ulama Surabaya, 2025)
The rapid growth of mobile gaming, which accounts for a significant portion of the global gaming market, necessitates optimal UI/UX design to maintain competitive advantage and player retention. One of the most popular games in Indonesia is Genshin Impact, which recorded 6,857,493 downloads on the Indonesian Playstore and Appstore as of September 2022. Research concerning UI/UX in games like Genshin Impact has become increasingly vital due to the growing emphasis on user engagement and accessibility within the gaming industry. The specific challenges of effectively designing UI/UX for complex open-world games, such as Genshin Impact, present significant opportunities for further exploration. Shrouded Buana is a game developed with Genshin Impact as its primary reference. This research focuses on avoiding various UI/UX-related issues in Genshin Impact. The Design Thinking framework is employed as the methodology for developing the UI/UX of Shrouded Buana. The usability level of the Shrouded Buana UI/UX is measured using the Cognitive Walkthrough (CW) method. the Cognitive Walkthrough is conducted through playtesting, where 30 users are presented with specific scenarios of tasks to complete. The Shrouded Buana's average task completion time (TCT) across all scenarios is 96,71%. The Average of Shrouded Buana's Task Completion Time is 5,15 s. Its mean Shouded Buanas's UI UX are very good so can support respondents to finish all scenarios quickly.